Phytochemical studies of Garcinia eugenifolia wall., G. nitida pierre., G. mangostana L., and Morinda citrifolia L., and their biological activities - Jong, Vivien Yi Mian (2012)
Phytochemical studies were carried out on four plants, Garcinia eugenifolia, Garcinia nitida, Garcinia mangostana and Morinda citrifolia. The chemical investigation has resulted in the isolation of 22 compounds which covered xanthones, triterpenoids and quinones. These compounds were isolated using common chromatographic techniques and were identified using spectroscopic experiments such as NMR, MS, IR and UV. The roots of Garcinia eugenifolia afforded six compounds comprising three triterpenoids, b-sitosterol (145), magniferolic acid (147) and euphadienol (148); two methanone, (3’-hydroxyphenyl)(2,4,6-trihydroxyphenyl) methanone (149) and (3,4-dihydroxyphenyl)(3-hydroxy-5-methoxyphenyl)methanone (150); and a xanthone,1,6-dihydroxy-7-methoxy-6’,6’-dimethyl-2H-pyrano[2’,3’:3,2]-xanthone (146). (3,4-dihydroxyphenyl)(3-hydroxy-5-methoxyphenyl)methanone (150) was isolated as a new compound. Besides this, the major compound, magniferolic acid (147) was isolated for the first time from Garcinia eugenifolia. Meanwhile, the roots of Garcinia nitida afforded a new compound 1,6-dihydroxy-5-methoxy-6,6-dimethylpyrano[2’,3’:2,3]-xanthone (151), together with three known xanthones and two common triterpenoids, inophyllin B (152), caloxanthone A (154), rubraxanthone (156) stigmasterol (153) and friedelin (155). Garcinia mangostana (roots) provided three pure compounds, a-mangostin (157), b-mangostin (158) and cowagarcinone B (160). b-mangostin was isolated as the major compound from the roots of Garcinia mangostana. Acetylation of b-mangostin (158) successfully yielded 1-hydroxy-3,7-dimethoxy-2,8-bis(3-methyl-2-butenyl)-9Hxanthen-9-one-6-acetate (159) as the product. Meanwhile, purification of the roots of Morinda citrifolia using chromatotron gave seven anthraquinones, damnacanthal (161), nordamnacanthal (162), sorandidiol (163), rubiadin (164), 1-hydroxy-2-methylanthraquinone (165), 2-ethoxy-1-hydroxyanthraquinone (166) and rubiadin-1-methyl ether (167). Cytotoxic tests were carried out using HeLa, MCF-7 and HL-60 cell lines on the crude extracts of Garcinia eugenifolia and Garcinia nitida. The pure compounds from all the four plants were assayed against HT-29 (Human Colorectal Cancer) and A549 (Human Lung Cancer). Garcinia eugenifolia were found to show moderate cytotoxicity with IC50 values ranging from 11 to 77 μg/mL for HeLa and MCF-7 cell lines. Meanwhile, for the HL-60 cell line, the hexane and ethyl acetate extracts of Garcinia eugenifolia indicated strong cytotoxicities with IC50 values of 1.9 μg/mL and 2.5 μg/mL respectively. For Garcinia nitida, the leaf extracts showed strong cytotoxic activity with IC50 values of 4 and 7 μg/mL respectively towards the HeLa and MCF-7 cell lines. However, the crude extract of the roots and twigs of Garcinia nitida was found to be inactive to MCF-7 activity test and weak cytotoxic activity against the HeLa cell line. Twelve pure compounds were subjected to cytotoxic assays using HT-29 and A549 cell lines. Magniferolic acid (147) gave IC50 values of 4.8 and 4.7 μg/mL respectively towards HT-29 and A549 cell lines while euphadienol (148) gave an IC50 value of 2.7 μg/mL towards the A549 cell line but showed moderate inhibition to HT-29 cell line. Meanwhile, 2-ethoxy-1-hydroxyanthraquinone (166) gave strong cytotoxicities (IC50 = 4.5 μg/mL) towards HT-29 but moderate activities (11.2μg/mL) against A549. Both damnacanthal (161) and nordamnacanthal (162) showed moderate inhibitory activities (IC50 <10 μg/mL) towards HT-29 cell line. The antimicrobial activity test was also carried out using five pathogenic bacteria,namely, Staphylococcus aures, Pseudomonas aeruginosa, Clostridium difficile,Streptococcus pyogenes and Escherichia coli. It was observed that most of the crude extracts from both Garcinia species exhibited strong inhibitory activities against the microbes. The only weak activity observed was for the Staphylococcus aures microbe for both methanol and ethyl acetate extracts of Garcinia nitida with an inhibitory diameter ranging from 4 to 8 mm. The DPPH antioxidant assay was carried out for both Garcinia eugenifolia and Garcinia nitida. Of all the tested extracts of Garcinia eugenifolia and Garcinia nitida, only the methanol extract from Garcinia eugenifolia stem bark and leaves exhibited moderate antioxidant activity (EC50 = 21.1 and 29.5 μg/L) when compared to ascorbic acid with EC50 values of 15.32 μg/L. As for total phenolic content, the twigs of Garcinia eugenifolia had the highest total phenolic content of 0.2322 ± 0.059 μg GAE/mg extract, followed by the roots (0.2274 ± 0.067 μg GAE/mg extract) and stem (0.2138 ± 0.013 μg GAE/mg extract).